Analisis Faktor Gaya kepemimpinan Kepala Ruangan terhadap Kinerja Perawat di Ruangan Rawat Inap Kelas 3 - Redo Widhio Mahatvavirya; Ermi Girsang (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The role of nurse leadership style has a large influence on nurses' work motivation. This is because the leadership of nurses in a good room will increase nurse job satisfaction, improve leadership performance is not good, it will increase the level of nurse job satisfaction. Some previous studies suggest that leadership is one of the main factors that improves performance because it is a driving force for all the resources within an organization. In leadership itself there are several parts of leadership that affect performance such as leadership style, leadership nature, type of leadership, work motivation, empowerment, work environment, organizational culture, leadership quality, and organizational commitment. Research conducted to look for analysis. Leadership style towards the performance of nurses in class 3 inpatient rooms of RSPH in 2018. This research is a type of quantitative research using cross sectional. The sample in the study amounted to 110 nurses in the room. Data collection techniques in research using questionnaires. The results of the study were obtained from studies involving communication factors (p = 0.001), planning (p = 0,000), direction (p = 0,000), and work discipline (p = 0,002) with the help of nurses in class 3 RSPH hospitalization. The conclusion of this study of the four revised variables is one of the most dominant variables affecting the work of nurses in class 3 inpatient rooms of RSPH in 2018, namely directing work by the head of the room